Do anti-HIV drugs pose a threat to photosynthetic microorganisms?. (November 2022) - Gomes, Marcelo Pedrosa; Kubis, Gabrielly Cristina; Kitamura, Rafael Shinji Akiyama; Figueredo, Cleber Cunha; Nogueira, Keite da Silva; Vieira, Fabio; Navarro-Silva, Mario Antônio; Juneau, Philippe
Abstract: We investigated the occurrence and risk assessment of three anti-HIV drugs [(tenofovir (TNF), lamivudine (LMV) and efavirenz (EFV)] in urban rivers from Curitiba (Brazil), as well as the individual and combined effects of their environmental representative concentrations on the freshwater periphytic species Synechococcus elongatus (Cyanobacteria) and Chlorococcum infusionum (Chlorophyta). The three studied drugs, except TNF, were found in 100% of the samples, and concentrations in samples ranged from 165 to 412 ng TNF L −1, 173–874 ng LMV L −1 and 13–1250 ng EFV L −1 . Bioassays using artificial contaminated water showed that at environmental concentrations, TNF and LMV did not represent environmental risks to the studied photosynthetic organisms. However, EFV was shown to be toxic, affecting photosynthesis, respiration, and oxidative metabolism. The studied drugs demonstrated interactive effects. Indeed, when submitted to the combination of TNF and LMV, decreased photosynthesis was observed in C. infusionum cells. Moreover, the toxic effects of EFV were amplified in both species when TNF and/or LMV were added to the media. The simultaneous presence of TNF, LMV and EFV in environmental matrices associated with their interactive effects, lead to increased toxicological effects of water contaminated by anti-HIV drugs and thus to an ecological threat to photosynthetic microorganisms. Graphical abstract: Image 1 Highlights: Simultaneous concentrations of TNF, LMV and EFV were found in urban rivers. At the found concentrations, only EFV represent risks to S. elongatus and C. infusionum . TNF, LMV and EFV show integrative effects. Toxic effects of EFV were amplified by LMV and EFV.